Allergic contact dermatitis in mice with interleukin-6 deficiency in dendritic cells - E. A. Gorshkova; A. D. Medvedovskaya; E. O. Gubernatorova (Медицинская иммунология, 2025)
Contact dermatitis is a disease characterized by skin inflammation caused by external agents, most commonly, allergens. Patients with contact dermatitis have impaired skin barrier function, causing permeability of the epidermis layer. Haptens, including oxazolone, are the small molecules that easily penetrate the epidermal barrier. When oxazolone binds to the tissue proteins, new antigenic conformations are formed, triggering an immune response and, subsequently, the development of allergic contact dermatitis. The pathogenic role of interleukin-6 in the development of contact dermatitis has been previously described in various murine models. Dendritic cells (DC), along with keratinocytes, are an important source of IL-6 in the skin. Moreover, DC as an antigen-presenting cells are involved in the development of allergic reaction. To establish the functional role of IL-6 from DC in development of allergic contact dermatitis, we induced dermatitis in the knockout mice with deficiency of IL-6 in dendritic cells (CD11c-IL-6 KO), and in wild-type control mice by applying oxazolone to the abdominal skin and then to the skin of the ears. Mice with deficiency of IL-6 from dendritic cells had more pronounced symptoms of skin inflammation than wild-type mice after sensitization with oxazolone. Thus, IL-6 produced by dendritic cells seems to have protective and regulatory functions in allergic contact dermatitis. Implementation of these functions may be mediated by TGF-β, whose expression was reduced in mice with tissue-specific IL-6 knockout in dendritic cells. TGF-β is an important regulatory cytokine that controls the balance of effector and regulatory T cell populations. Moreover, TGF-β is important for the resolution of inflammation and tissue healing. At the same time, the lack of difference in IL-4 and IL-17a expression between CD11c-IL-6 KO and wild type mice suggests that the Th2 and Th17 branches of the cellular response were not affected in highly susceptible mice with IL-6-deficiency in dendritic cells. The effects of systemic IL-6 deficiency shown in various models of dermatitis suggest a predominantly pathogenic role of this cytokine in the development of allergic contact dermatitis. Our data suggests that dendritic cells may serve as sources of “protective” IL-6 activity, participating not only in the development of the immune response but also in repair and maintenance of skin barrier functions.